La educación inicial y su influencia en el desarrollo de la motricidad fina el los niños y niñas de los primeros años de educación básica de las escuelas 23 de Abril y Guadalupe Fernández de Castro de los cantones Machala y el Guabo, periodo lectivo 2014 - 2015. - Taday Castro, Lizzeth Carolina (2015)
The methodological strategies used by teachers in early childhood education are instruments that have great impact on the acquisition of skills and psychomotor skills of children to successfully face the survival and specifically the educational process, which begins with admission to formal education , therefore it is essential that teachers in preschool successfully manage the methodological toolbox, so accordingly can choose custom fit those which are most effective for each student, according to their personal characteristics , since not all children are equal, are unique beings that require unique treatment. In the study, the need to improve strategies used by teachers of early childhood education as a priority pathway to achieve the development of the student is determined. You need to create awareness among teachers of the importance of developing fine motor skills in students because it is the basis for the further development of reading and writing. This will allow to analyze the development of fine motor skills in students. The training of teachers for active management strategies and integrative motivation is needed to achieve the development of fine motor skills. The proposed workshop teaching update, arises from a research process in which it is seen that although they use different teaching techniques for developing motor skills, where the game as a methodological strategy used to promote meaningful learning that constitute permanent challenges to advance the process of learning.